ANALISIS PENDAPATAN DAN RISIKO USAHA PEMBIBITAN ALPUKAT (Persea americana) PADA CV. KARYA TANI MANDIRI DI KABUPATEN LANGKAT - Pratama, Agus; Rini Mastuti; Rozalina (grafting, 2025)
The aim of the research is to analyze the income and risks of the CV avocado breeding business. Karya Tani Mandiri in Langkat Regency. The research method used in this research is the case study method. Research data analysis includes; cost analysis, revenue, income, R/C ratio, BEP and risk analysis. Results of analysis of avocado breeding business income at CV. Karya Tani Mandiri Langkat Regency in 2022 is IDR 335,291,500. The results of the BEP analysis are BEPProduction calculated as 6,531 seeds/year < actual production 15,200 seeds/year so BEP has been achieved and BEPRupiah calculated as Rp. 27,931/seed < actual price Rp. 65,000/kg so BEP has been achieved. The results of the R/C ratio analysis are an R/C Ratio value of 1.79 > 1, meaning the business is profitable and worth continuing. The results of the risk analysis are production risk, the CVProduction = 0.14 < 0.5, meaning it has a small risk, the risk of receiving the CVRevenue = 0.13 < 0.5, meaning it has a small risk and the income risk the CVIncome = 0.3 < 0.5 and the lower limit value (L) of income of IDR 10,761,063 means that the CV avocado breeding business. Karya Tani Mandiri has small risks and is profitable (positive income).